2016
DOI: 10.1007/s10157-016-1340-2
|View full text |Cite
|
Sign up to set email alerts
|

Mizoribine therapy combined with steroids and mizoribine blood concentration monitoring for idiopathic membranous nephropathy with steroid-resistant nephrotic syndrome

Abstract: BackgroundWe designed a prospective and randomized trial of mizoribine (MZR) therapy combined with prednisolone (PSL) for idiopathic membranous nephropathy (IMN) with steroid-resistant nephrotic syndrome (SRNS).MethodsPatients with IMN were divided into 2 groups, and MZR combined with PSL was administered for 2 years. PSL was initially prescribed at 40 mg/day and tapered. MZR was given once-a-day at 150 mg and 3-times-a-day at 50 mg each to groups 1 and 2. Serum MZR concentrations from 0 to 4 h after administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
0
4
0
1
Order By: Relevance
“…Rituximab was compared with non-immunosuppressive therapy (1 trial, 75 participants) [ 11 ]. Mizoribine was compared with steroid monotherapy (1 trial, 36 participants) [ 43 ] and also against different doses of mizoribine (1 trial, 37 participants) [ 66 ]. Azathioprine was compared with non-immunosuppressive therapy (2 trials, 23 participants) [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Rituximab was compared with non-immunosuppressive therapy (1 trial, 75 participants) [ 11 ]. Mizoribine was compared with steroid monotherapy (1 trial, 36 participants) [ 43 ] and also against different doses of mizoribine (1 trial, 37 participants) [ 66 ]. Azathioprine was compared with non-immunosuppressive therapy (2 trials, 23 participants) [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that MN has a high spontaneous remission rate ( Saito et al, 2017 ), and it can be concluded that some patients achieve spontaneous remission. In order to exclude such potential spontaneous remission cases, we reviewed the proteinuria and serum albumin levels 6°months prior to the TCM treatment.…”
Section: Resultsmentioning
confidence: 99%
“…W. Chen et al ( Chen et al, 2013 ) reported a benefit of combining TAC with prednisone in treating 14 adults Chinese RIMN patients, that remission was attained in 11/14 patients (78.6%: CR 35.7% and PR 42.9%) at the end of follow-up. T. Saito et al ( Saito et al, 2017 ) treated 19 patients with Mizoribine (MZR) in combination with prednisolone, and CR was attained in only 10/19 (52.6%) patients after more than 2°years of treatment. F.B.…”
Section: Discussionmentioning
confidence: 99%
“…Монотерапию ГКС проводили в отдельных, редких случаях, в основном при противопоказаниях к назначению цитостатических препаратов. Одним из средств лечения больных МН является ритуксимаб, который применен в комбинации с цитостатиками или в качестве монотерапии в небольшой части случаев и имеет определенные перспективы [55][56][57] наряду с такролимусом, мизорибином и адренокортикотропным гормоном [58][59][60].…”
Section: таблица 3 клинико-морфологические показатели в группе ремисunclassified